2023
DOI: 10.1111/hae.14751
|View full text |Cite
|
Sign up to set email alerts
|

Health and quality of life of patients with haemophilia: A national study of 124 Danish men

Abstract: Purpose: In the past decades, haemophilia treatment has greatly improved the health of persons with haemophilia (PWH). This study compares PWH to the general population on social conditions and health. Methods:In December 2021, all Danes with moderate or severe haemophilia A or B, or von Willebrands disease type 3 were invited to participate in an online selfreport survey concerning sociodemographic factors, self-rated health, teeth status, chronic health conditions, symptoms and loneliness. This study compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our ndings demonstrate the actual status of HA patients, including singleness, low employment and low educational attainment, as shown in Table 1, and are more likely to be associated with nancial burden and physical disability. However, a Danish study showed that by controlling for age differences, no signi cant differences were found in education and marital levels between PWH and the general population, and employment rates for PWH were signi cantly lower in 45-64 year olds than in their peers of the same age, but no differences were found in the younger (16-44 year old) group [7]. This may be because our analysis is for all age groups, and there is still a degree of wealth disparity in our large population.…”
Section: Discussionmentioning
confidence: 98%
“…Our ndings demonstrate the actual status of HA patients, including singleness, low employment and low educational attainment, as shown in Table 1, and are more likely to be associated with nancial burden and physical disability. However, a Danish study showed that by controlling for age differences, no signi cant differences were found in education and marital levels between PWH and the general population, and employment rates for PWH were signi cantly lower in 45-64 year olds than in their peers of the same age, but no differences were found in the younger (16-44 year old) group [7]. This may be because our analysis is for all age groups, and there is still a degree of wealth disparity in our large population.…”
Section: Discussionmentioning
confidence: 98%
“…49 Some encouraging data arose from a self-reported survey comparing Danish PWH from 16 to 84 years of age versus the Danish general population on selected indicators of HRQoL, which revealed that PWH now resembles the general population in areas such as marriage and education compared with earlier surveys. 50 However, even for young PWH, the disease still imposes poorer levels of employment compared with the general population and a significant burden from arthropathy and pain in extremities and joints.…”
Section: Pain Burden In Pwhmentioning
confidence: 99%